2012
DOI: 10.1080/00103624.2012.701687
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal Application to Arable Soil: Effects on CO2Emissions

Abstract: Activated carbon and commercial household charcoal were added to soil in a 36-day incubation study at 20 • C measuring carbon dioxide evolution. The black carbon materials were found to decompose slowly, releasing between 1.4% and 0.8% of their carbon content per year, respectively. The main experiment tested whether the black carbon additions to soil (2% and 4% by mass) affected decomposition of selected substrates in soil, both respiration dynamics and total respiration. The results indicated that the black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The unrecovered BC of at least 24% in the top 20 cm of soil can be attributed to (i) loss due to decomposition, (ii) migration as solid BC or dissolved organic matter to soil layers below 20 cm depth, which were not sampled, and (iii) lateral loss due to both water and wind erosion of the surface soil. The decomposition rate of BC produced within the same temperature range as our BCs has been reported to be small, with values in the range of 1% yr À1 within the first year of application (Carlsson et al, 2012;Kuzyakov et al, 2009;Luo et al, 2011). Some of the studies e.g.…”
Section: Discussionmentioning
confidence: 60%
“…The unrecovered BC of at least 24% in the top 20 cm of soil can be attributed to (i) loss due to decomposition, (ii) migration as solid BC or dissolved organic matter to soil layers below 20 cm depth, which were not sampled, and (iii) lateral loss due to both water and wind erosion of the surface soil. The decomposition rate of BC produced within the same temperature range as our BCs has been reported to be small, with values in the range of 1% yr À1 within the first year of application (Carlsson et al, 2012;Kuzyakov et al, 2009;Luo et al, 2011). Some of the studies e.g.…”
Section: Discussionmentioning
confidence: 60%
“…Different studies have observed increases in soil respiration (Kolb et al ., ; Zavalloni et al ., ; Belyaeva & Haynes, ; Castaldi et al ., ; Quilliam et al . ; Ventura et al ., ); although decreases (Dempster et al ., ; Paz‐Ferreiro et al ., ; Carlsson et al ., ) or no change have also been observed (Galvez et al ., ; Bamminger et al ., ).…”
Section: Introductionmentioning
confidence: 86%
“…Observed effects of biochar on edaphic microbial processes are often conflicting. Different studies have observed increases in soil respiration (Kolb et al, 2009;Zavalloni et al, 2011;Belyaeva & Haynes, 2011;Castaldi et al, 2011;Quilliam et al 2012;Ventura et al, 2014); although decreases (Dempster et al, 2011;Paz-Ferreiro et al, 2011;Carlsson et al, 2012) or no change have also been observed (Galvez et al, 2012;Bamminger et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although biochar from organic residues principally can be used as a soil improving product (e.g. Carlsson et al 2012 ; Parvage et al 2013 ), metal contents in biochar from sewage sludge are too high (e.g. Song et al 2014 ) and similar to ash limiting its use as a soil amendment.…”
Section: Future Waste Management In Cities—from Direct Waste Recyclinmentioning
confidence: 99%